SALIVARY HUMORAL AND CYTOKINE IMMUNE INDICATORS IN CHILDREN WITH RECURRENT HERPETIC STOMATITIS, INCLUDING THOSE WITH CONCURRENT ALLERGIC DISEASES - Razikova Dilnoza Kadirovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Recurrent herpetic stomatitis (RHS) is a common pediatric infection caused by herpes simplex virus type 1, often associated with impaired mucosal immunity. When accompanied by allergic diseases, the severity of immune dysregulation may increase. This study investigated local humoral and cytokine immunity in children with RHS, both isolated and combined with allergic conditions. Methods: A total of 120 children aged 1–7 years were examined and divided into three groups: healthy controls (n=40), RHS without allergy (n=40), and RHS with allergy (n=40). Saliva samples were collected and analyzed for secretory IgA (sIgA), lysozyme, total IgA, IgM, IgG, IgE, as well as cytokines IL-6 and IL-10 using ELISA. Statistical analysis was performed to compare groups. Results: Children with RHS demonstrated a significant decrease in sIgA and lysozyme levels compared with controls, which was more pronounced in allergic patients (sIgA: 207.17 vs. 90.57 µg/mL; lysozyme: 159.76 vs. 76.71 µg/mL, p<0.001). Humoral immunity was altered: IgA decreased nearly twofold in the RHS+allergy group, while IgM increased more than twofold. IgG was elevated only in RHS without allergy, whereas IgE was strongly elevated in both patient groups, with the highest levels in comorbid cases (246.29 µg/mL). Cytokine profiling revealed marked IL-6 elevation (up to 4.58-fold above controls) and a parallel but less intense rise in IL-10. Conclusion: RHS in children is associated with impaired local immunity, antibody imbalance, and cytokine dysregulation. The coexistence of allergic diseases aggravates immune deficiencies, amplifies inflammatory responses, and further weakens mucosal protection. These findings highlight the importance of comprehensive immune monitoring in pediatric RHS, particularly under allergic comorbidity.